Mechanism Of Formation and Future of Development of Free Economic Zones in Agriculture of Uzbekistan (Texas Journal of Multidisciplinary Studies, 2021)
This article describes the Bukhara-Agro, Kasan-Agro and Karakalpak-Agro Free Economic Zones (hereinafter referred to as FEZs) established in Uzbekistan and their role in the country's economy, in particular in agriculture. rni is considered. In particular, in these FEZs to attract foreign and domestic direct investment to organize modern greenhouses, including hydroponic technologies, on a cluster basis, as well as agricultural products. issues of environmental protection in the process of cultivation and processing. In recent years, the country's population has been growing steadily, land and water resources have been declining for various reasons, the demand for agricultural food products has increased, and the government has been asked to ensure food security. puts. This article aims to address the above issue, albeit partially, to enhance the role of agro-economic FEZs in the agricultural sector in the country's economy and to create new economic zones in this area. While highlighting the importance of our goal in this regard, the following tasks have been set: - Disclosure of the benefits of the organization of agro-economic free economic zones; - employment and living standards of the population; - regional economic growth through the establishment of agro-economic free economic zones; In declaring these goals and objectives, decrees and resolutions of the President of the Republic of Uzbekistan, as well as decisions of the Cabinet of Ministers, as well as various scientific works and literature were used, as well as research methods such as geographical comparison, systematic content, cartography and balance. During the study of the topic, the necessary proposals and recommendations were made in the field of agriculture, established in our country, in these SEZs "Bukhara-agro", "Koson-agro" and "Karakalpak-agro".